2002
DOI: 10.1080/000164802320396321
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Suppresses MUC5AC Gene Expression and Mucin Secretion in Nasal Epithelial Cells

Abstract: Recently, it was found that IL-13 is involved in allergic inflammation and mucus hypersecretion in in vivo animal models. However, the role of IL-13 in in vitro cellular models has yet to be determined. This study aimed to investigate the direct effect of IL-13 on mucin gene expression and mucin secretion in cultured normal human nasal epithelial cells. After treatment with IL-13, total mucin and MUC5AC mucin levels were measured using an immunoblotting assay. MUC2, MUC5AC and MUC8 mRNA expression were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
16
2
Order By: Relevance
“…Because IL-4/IL-13Rs are expressed on a wide range of cell types, subsequent studies have attempted to determine whether these cytokines act directly on epithelial cells to induce mucus metaplasia. Some studies showed IL-4 or IL-13 treatment of cultured airway epithelial cells increased mucus production and/or expression of transcripts encoding the major airway mucin Muc5ac (30 -34), but others did not (35)(36)(37)(38)(39)(40). IL-4 and IL-13 might also induce mucus production indirectly, via their ability to recruit and activate inflammatory cells such as neutrophils and eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…Because IL-4/IL-13Rs are expressed on a wide range of cell types, subsequent studies have attempted to determine whether these cytokines act directly on epithelial cells to induce mucus metaplasia. Some studies showed IL-4 or IL-13 treatment of cultured airway epithelial cells increased mucus production and/or expression of transcripts encoding the major airway mucin Muc5ac (30 -34), but others did not (35)(36)(37)(38)(39)(40). IL-4 and IL-13 might also induce mucus production indirectly, via their ability to recruit and activate inflammatory cells such as neutrophils and eosinophils.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies were performed on cell lines or in animal models, and the data on primary epithelial cells are minimal. Recently, IL-13 has been shown to decrease MUC5AC gene expression and mucin secretion in cultured nasal epithelial cells (113). In another study, Chen et al (114) tested a panel of cytokines on primary human tracheal epithelial cells.…”
Section: Cytokine-induced Mucin Productionmentioning
confidence: 99%
“…121 It however decreased MUC5AC expression in human nasal epithelial cells. 122 Other Th2 cytokines like IL-6, IL-9, IL-10 and IL-22 have also been shown to regulate mucin expression. IL-6 increased the expression of the gel-forming mucins, MUC2, MUC5AC, MUC5B and MUC6 and stimulated secretion in LS180 cells.…”
Section: Regulation Of Mucins By Cytokinesmentioning
confidence: 99%